Cellular rejection of pancreaticoduodenal graft - A. V. Pinchuk; R. V. Storozhev; I. V. Dmitriev; N. V. Shmarina; G. A. Nefedova; R. Sh. Muslimov; Yu. S. Teterin (Вестник трансплантологии и искусственных органов)
Aim. The evaluation of donor’s duodenum histological examination in diagnosis of pancreaticoduodenal graft rejection.Materials and methods. The 35-yo patient with terminal diabetic nephropathy undergone simultaneous retroperitoneal kidney and pancreas transplantation  with enteric exocrine drainage of the graft via inter-duodenal anastomosis. When performing the esophagogastroduodenoscopy 2 years posttransplant we  implemented histologic examination of the duodenum of the graft.Results. We diagnosed and verified severe cellular rejection of pancreaticoduodenal graft. Successful etiopathogenetic treatment of acute  rejection of the graft (pulse therapy with glucocorticoids) was performed.Discussion. The diagnostic value of donor’s duodenum morphological examination in the diagnosis of pancreaticoduodenal graft  rejection, the efficacy of anti-rejection treatment were performed in this case.